Submaximal substrate utilization is unaffected by acute and chronic hypoxia when expressed relative to maximal oxygen uptake - Lundby, C.; van Hall, G. (The Journal of Physiology, 2002)
Altitude exposure has long been considered to induce changes in substrate utilization during submaximal exercise in humans, leading to an enhanced reliance on carbohydrates (CHO) (Roberts et al. 1996). Since VO2,max decreases with increasing altitude, a given intensity will be relatively higher when performed at altitude. Thus the question arises whether a difference in substrate utilization still exists when aerobic energy turnover is normalized for differences in VO2,max. Six equally trained sea level male residents participated in the study. Ethical approval was obtained. All subjects performed 60 min cycle ergometer exercise on five occasions: (1) at sea level (47 % VO2,max); in acute hypoxia at (2) an absolute workload (59 % VO2,max) and (3) a relative workload (48 %VO2,max); after 3 weeks of chronic hypoxia at 4100 m.a.s.l. at (4) an absolute workload (61 % VO2,max) and (5) a relative workload (50 % VO2,max). On each occasion the subjects reported to the laboratory 12 h ostabsorbtive and were fed 0.7 g cornflakes per kg body weight with a free amount of skimmed milk. Exercise was initiated exactly 2 h after finishing the meal. Pulmonary gas exchange and blood samples were obtained at rest and after 15, 30, 45 and 60 min of exercise. Statistical difference (P < 0.05) between trials was tested by two-way ANOVA and Tukey's Studentized range test. Relative to total energy turnover, CHO oxidation is unchanged during hypoxic exposure compared with sea level when the workload is expressed as a percentage of VO2,max, whereas it is increased at the same absolute workload (Fig. 1). By expressing exercise intensity as a percentage of VO2,max, this study shows that substrate utilization is not affected by acute or chronic high altitude exposure, and we suggest that the mechanisms regulating substrate utilization in hypoxia do not differ from those at sea level.